2017
DOI: 10.1002/pmic.201700164
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Extracellular Matrix and Signal Mechanotransduction to Epithelial Cell Damage in Inflammatory Bowel Disease Patients: A Proteomic Study

Abstract: This study utilizes 2D-DIGE (difference gel etrophoresis), isotope-coded protein labeling and biochemical assays to characterize protein alteration in ulcerative colitis (UC) and Crohn's disease (CD) in human epithelial cell and mucosal biopsies in inflammatory bowel disease (IBD)-affected patients. The aim of this study is to identify the key molecular signatures involved in epithelial cell structure of IBDs. In non-inflamed UC (QUC) keratins, vimentin, and focal adhesion kinase (7) increased, whereas vinculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 70 publications
3
30
0
Order By: Relevance
“…Collagen alpha-4 (VI) chain was found deiminated in wandering albatross plasma. It is an extracellular matrix protein [206], is found in lymphoid tissues [207] and has roles, amongst others, in cellular and mucosal immunity and inflammatory diseases such as ulcerative colitis and membranous glomerulonephritis [208,209]. In birds, it has roles in CNS development relating to plasticity and axon growth in the chicken [210].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen alpha-4 (VI) chain was found deiminated in wandering albatross plasma. It is an extracellular matrix protein [206], is found in lymphoid tissues [207] and has roles, amongst others, in cellular and mucosal immunity and inflammatory diseases such as ulcerative colitis and membranous glomerulonephritis [208,209]. In birds, it has roles in CNS development relating to plasticity and axon growth in the chicken [210].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that MSN, entailed in connections of major cytoskeletal structures to the plasma membrane, A1BG, and two proteoforms of FGB increased, suggesting that a matrix remodeling characterized DN‐E3G3 . Previous studies from our group in inflammatory bowel disease (IBD) patients, in COL6A1 deficient animal models and mypoatic patients with mutation in COL6A1, highlighted the role of matrix, metabolism, and structural remodeling in disease onset and progression. A similar “mechanosignaling” appears active also in DN‐E3G3 suggesting that matrix remodeling can be able to perceive physical and chemical signals activating focal adhesion that sense the rigidity of the extracellular matrix .…”
Section: Discussionmentioning
confidence: 59%
“…The 2D‐DIGE is a top‐down proteomic technique for the study of a fraction of metabolic, structural, cytoskeletal, and cell signaling protein levels and provides a picture of proteoforms and PTMs of undigested proteins . Considering E3G3 characteristics according to tumor hormone receptors expression, ECM proteins, in particular COL6A1, were more abundant in DN‐E3G3 than in E3G3 BCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In IBD COL6α1, COL6α2 and COL6α3 chains are elevated in the intestinal tissue in patients with CD and UC, and COL6 has been demonstrated to be involved in the integrity of the epithelial barrier 20,21 . It has previously been demonstrated that COL6 turnover was elevated in luminal CD and stricturing CD compared to fistulizing CD 22 .…”
mentioning
confidence: 99%